Asthma-Targeted MURs: How Confident are Community Pharmacists in Delivering Different Interventions? - Reem Kayyali; Ifrah Ali; Asma'a Al-Hindawi; Iman Hesso; Finlay Royle (MDPI AG, 2019)
This study aimed to identify and determine the confidence level of community pharmacists in providing different interventions during asthma-targeted medicine use reviews (MURs). A self-administered questionnaire was posted to 487 pharmacies accredited to provide the service, across Greater London, Southampton, Cornwall, Sheffield and Norwich. A total of 122 responses were obtained, giving a response rate of 25% (122/487). Around half of the community pharmacists (51.6%) were providing more than 60 asthma-targeted MURs annually with inhaler technique being the most offered intervention and stepping up/down therapy being the least. The majority of community pharmacists (94.3%) were confident in providing inhaler technique advice, followed by smoking cessation (91%). However, confidence was less with relevant vaccination (61.5%) and stepping up/down patients’ therapy (56.6%). Confidence level can vary between community pharmacists regarding different interventions provided during respiratory MURs. The results stress the need to promote community pharmacists’ confidence in providing interventions such as stepping up/down therapy during asthma-targeted MURs. Additional research in this field is highly recommended in order to evaluate community pharmacists’ confidence level on a national scale and to determine the factors influencing it. The study also suggests that provision of different interventions during respiratory MURs can be related to how community pharmacists perceive their role.